2020
DOI: 10.3390/su12083115
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Efficient Energy Smart Home Management System for Renewable Energy Resources

Abstract: This article provides a fuzzy expert system for efficient energy smart home management systems (FES-EESHM), demand management, renewable energy management, energy storage, and microgrids. The suggested fuzzy expert framework is utilized to simplify designing smart microgrids with storage systems, renewable sources, and controllable loads on resources. Further, the fuzzy expert framework enhances energy and storage to utilize renewable energy and maximize the microgrid’s financial gain. Moreover, the fuzzy expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The movement data are then translated into action commands for computers to execute, and human activity recognition code is an important and effective tool [ 20 , 21 , 22 ]. The composition of co-fabrication spaces requires smart sensors and apps to create opportunities for more in-depth environmental monitoring compared to formal monitoring networks and to involve the public in environmental monitoring through participatory data collection and monitoring systems [ 23 ].…”
Section: Related Researchmentioning
confidence: 99%
“…The movement data are then translated into action commands for computers to execute, and human activity recognition code is an important and effective tool [ 20 , 21 , 22 ]. The composition of co-fabrication spaces requires smart sensors and apps to create opportunities for more in-depth environmental monitoring compared to formal monitoring networks and to involve the public in environmental monitoring through participatory data collection and monitoring systems [ 23 ].…”
Section: Related Researchmentioning
confidence: 99%
“…Maiti found that the features of miners’ workplace have a significant impact on the occurrence of accidents, such as under noisy workplaces, miners cannot concentrate effectively and are prone to unsafe behaviors [ 53 ]. Furthermore, Zhang et al discussed the state of coal miners in different production environments and argued the detection of the coal mine environment has been a crucial part of coal mine production [ 54 ]. Additionally, Tuna et al discovered that the corporate safety climate and the importance of the organization to employees were negatively correlated with employees’ unsafe behaviors [ 55 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sales growth is one of the most important indicators to measure business growth (Wein et al 1998, Zhang et al 2020, Mika et al 2017. Therefore, this article chooses the annual sales of wood flooring products as the dependent variable to represent the growth of the company, and forms a reference series.…”
Section: Choice Of Dependent Variablementioning
confidence: 99%